COMPENSATION, ORGANIZATIONAL CULTURE, AND CADDIE PERFORMANCE: MEDIATING ROLE OF JOB SATISFACTION - Madani, Eka Putri; Masripah, Ipah; Amelia, Dahlia; Suhardaliyah, Suhardaliyah (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study addresses the growing need to enhance stewardship performance in the golf industry, particularly among caddies, whose role significantly impacts service quality and customer satisfaction. Despite the critical function of caddies at premium golf clubs, their performance remains underexplored in organizational behavior research. The purpose of this study is to examine the effects of compensation and organizational culture on caddie performance, with job satisfaction as a mediating variable, at Modern Golf & Country Club in Tangerang City. Using a quantitative approach, data were collected from 100 caddies through a structured questionnaire based on a Likert scale. A probability sampling technique was employed, and data were analyzed using SmartPLS 4 for structural equation modeling. Results indicate that compensation has a positive and significant effect on both job satisfaction (p = 0.001) and caddie performance (p = 0.006). Organizational culture positively influences job satisfaction (p = 0.000), though its direct impact on performance is not significant (p = 0.511). Job satisfaction significantly mediates the relationship between compensation and performance (p = 0.000), as well as between organizational culture and performance. This study contributes to both theory and practice by empirically validating job satisfaction as a key mechanism through which organizational factors influence frontline service performance in a niche leisure industry. The findings offer practical insights for golf club management to design better compensation systems and foster a supportive organizational culture to enhance caddie motivation and service excellence. This research is original in its focus on caddies—a largely overlooked workforce—in the Indonesian context, filling a gap in hospitality and sports management literature.